An ultraviolet aging resistant silicone rubber material for advanced manufacturing and a preparation method thereof

CN122958874APending Publication Date: 2026-10-23ZHEJIANG LEXUS NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611268618.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

有机紫外吸收剂存在易迁移析出、热稳定性差的问题;单一无机纳米粒子虽具备宽谱紫外屏蔽能力,但在硅橡胶基体中分散性差,且ZnO、TiO2等半导体氧化物在紫外光激发下易产生光生电子-空穴对,催化硅橡胶分子链降解,反而加速老化;层状矿物填料主要依赖物理反射和曲折路径阻隔紫外线,对UVA波段吸收不足

Benefits of technology

1.本发明通过绢云母片状基核的物理反射与曲折阻隔、ZnO-CeO2复合纳米层的宽谱化学吸收,以及外层有机紫外吸收基团的协同作用,使材料对UVA和UVB波段的屏蔽覆盖趋于完整;同时有机紫外吸收基团经化学接枝固定于复合物表面,迁移析出趋势显著降低,紫外防护耐久性趋于提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958874A_ABST
    Figure CN122958874A_ABST
Patent Text Reader

Abstract

The application discloses an anti-ultraviolet aging silicone rubber material for advanced manufacturing and a preparation method thereof, and relates to the technical field of polymer materials. The anti-ultraviolet aging silicone rubber material for advanced manufacturing comprises the following components in parts by mass: 100 parts of raw silicone rubber, 25-40 parts of reinforcing filler, 3-6 parts of structure control agent, 2-4 parts of crosslinking agent, 0.1-0.3 parts of catalyst, 0.06-0.12 parts of inhibitor and 4-8 parts of modified anti-ultraviolet compound. The synergistic effect of the physical reflection and zigzag barrier of the sericite flaky base core, the wide-spectrum chemical absorption of the ZnO-CeO2 composite nano layer and the outer organic ultraviolet absorption group makes the shielding coverage of the material to the UVA and UVB bands tend to be complete. Meanwhile, the organic ultraviolet absorption group is chemically grafted and fixed on the surface of the compound, the migration and precipitation trend is significantly reduced, and the ultraviolet protection durability tends to be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, specifically to an advanced manufacturing UV-resistant silicone rubber material and its preparation method. Background Technology

[0002] Silicone rubber materials are widely used in aerospace, photovoltaic module encapsulation, outdoor sealing, and advanced manufacturing due to their excellent high and low temperature resistance, weather resistance, electrical insulation, and biocompatibility. However, under long-term outdoor service conditions, silicone rubber molecular chains are prone to main chain breakage and side group oxidation under ultraviolet radiation, leading to material hardening, cracking, mechanical property degradation, and sealing failure, which severely limits its service life in harsh environments.

[0003] Currently, the main methods to improve the UV aging resistance of silicone rubber include adding organic UV absorbers, inorganic nano-shielding agents, and layered mineral fillers. Organic UV absorbers suffer from problems such as easy migration and precipitation, and poor thermal stability. While single inorganic nanoparticles possess broad-spectrum UV shielding capabilities, they exhibit poor dispersibility in the silicone rubber matrix. Furthermore, semiconductor oxides such as ZnO and TiO2 easily generate photogenerated electron-hole pairs under UV light excitation, catalyzing the degradation of silicone rubber molecular chains and accelerating aging. Layered mineral fillers primarily rely on physical reflection and tortuous paths to block UV rays, resulting in insufficient absorption of the UVA band. In addition, the interfacial compatibility between these functional fillers and raw silicone rubber is poor, easily leading to platinum-based catalyst poisoning, delayed crosslinking, or filler agglomeration during vulcanization, making it difficult to balance UV resistance efficiency with material mechanical properties.

[0004] Therefore, developing a modified UV-resistant composite filler that combines broad-spectrum UV absorption, inhibition of photocatalytic side reactions, and good compatibility with silicone rubber vulcanization systems has significant engineering application value for preparing high-performance, long-life, UV-resistant silicone rubber materials. Summary of the Invention

[0005] The purpose of this invention is to address the problems existing in the prior art by providing an advanced manufacturing material for UV-resistant silicone rubber and its preparation method. This material, through the introduction of a multi-level, multifunctional, synergistic modified UV-resistant composite, achieves broad-spectrum, high-efficiency UV absorption, suppresses photocatalytic side reactions, and exhibits good compatibility with the silicone rubber matrix and vulcanization system, thereby significantly improving the service life of silicone rubber in harsh outdoor environments.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: An advanced manufacturing UV-resistant silicone rubber material, by weight, comprises the following components: 100 parts of raw silicone rubber, 25-40 parts of reinforcing filler, 3-6 parts of structure control agent, 2-4 parts of crosslinking agent, 0.1-0.3 parts of catalyst, 0.06-0.12 parts of inhibitor, and 4-8 parts of modified UV-resistant composite.

[0007] The modified UV-resistant composite has a core-shell composite structure with sericite as the core. The surface of the core is loaded with a ZnO-CeO2 composite nanolayer. The ZnO-CeO2 composite nanolayer is coated with a SiO2 passivation layer. The surface of the SiO2 passivation layer is grafted with benzotriazole and benzophenone organic UV-absorbing groups and contains vinylsilane and polydimethylsiloxane compatible segments.

[0008] Furthermore, the modified UV-resistant composite comprises, by weight, the following components: 35-45 parts sericite powder, 18-28 parts zinc acetate dihydrate, 3-8 parts cerium nitrate hexahydrate, 10-18 parts urea, 20-35 parts tetraethyl orthosilicate, 3-6 parts γ-glycidyl etheroxypropyltrimethoxysilane, 4-8 parts 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-5 parts 2,4-dihydroxybenzophenone, 2-4 parts vinyltriethoxysilane, 6-12 parts hydroxyl-terminated polydimethylsiloxane, and 0.3-0.8 parts potassium carbonate.

[0009] Furthermore, the preparation method of the modified UV-resistant composite includes the following steps: S1. Add the sericite powder to the sodium hydroxide aqueous dispersion with a mass concentration of 3wt%, control the solid-liquid ratio to 1:10, stir for 1.5-3 hours at 50-65℃ and 400-600 r / min, filter, wash with deionized water until the pH of the filtrate is 7.0-8.0, dry at 80-100℃ for 4-6 hours, and pass through an 800-1250 mesh sieve to obtain surface-hydroxylated flake sericite.

[0010] S2. The surface-hydroxylated flaky sericite is dispersed in a mixture of deionized water and anhydrous ethanol in a mass ratio of 1:2, with the solid-liquid ratio controlled at 1:14. The mixture is stirred and ultrasonically dispersed at 600-900 r / min for 20-40 min. The zinc acetate dihydrate, cerium nitrate hexahydrate, and urea are added, and the temperature is raised to 78-88℃. The reaction is carried out for 3-5 h. After the reaction is completed, the mixture is filtered, washed, and dried at 100-120℃ for 3-5 h. Then, it is calcined at 300-360℃ for 1.5-2.5 h to obtain a flaky composite core with an in-situ ZnO-CeO2 synergistic ultraviolet absorption layer.

[0011] S3. The sheet-like composite core is added to a system composed of deionized water and anhydrous ethanol in a mass ratio of 1:5, the solid-liquid ratio is controlled at 1:10, the pH of the system is adjusted to 9.0-10.0, the temperature is 35-45℃, the stirring speed is 500-800 r / min, and the tetraethyl orthosilicate is added dropwise at a rate of 0.5-1.0 mL / min. After the addition is completed, the reaction continues for 3-5 h, and the mixture is allowed to stand for aging for 2-4 h. After filtration, washing with ethanol and drying at 90-110℃ for 4-6 h, a sheet-like core-shell intermediate with a silica passivation layer is obtained.

[0012] S4. Under nitrogen protection, the 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2,4-dihydroxybenzophenone, γ-glycidoxypropyltrimethoxysilane and potassium carbonate are added to anhydrous ethanol, the solid-liquid ratio is controlled at 1:9, and the reaction is carried out at 70-82℃ and 300-500r / min for 2-4h. After cooling, the insoluble matter is removed by filtration to obtain a composite organic ultraviolet absorption modified liquid containing silane end groups.

[0013] S5. Disperse the plate-like core-shell intermediate in the composite organic UV absorption modification solution, adjust the pH of the system to 4.5-5.5, add the vinyltriethoxysilane and hydroxyl-terminated polydimethylsiloxane dropwise, and graft and coat the mixture at 65-78℃ and 500-700r / min for 4-7h. Then filter, wash with anhydrous ethanol until the filtrate is colorless, vacuum dry at 85-105℃ for 6-10h, pulverize and pass through an 800-1250 mesh sieve to obtain the modified UV-resistant composite.

[0014] The sericite powder described in this invention forms a core layer for ultraviolet reflection and tortuosity blocking. ZnO-CeO2, in conjunction with the ultraviolet absorption layer, forms a broadband absorption shielding layer for UVA and UVB. The silica passivation layer isolates ZnO-CeO2 from the silicone rubber molecular chain and inhibits photocatalytic side reactions. The outer layer containing benzotriazole, benzophenone, and polydimethylsiloxane segments forms a migration-resistant siloxane-compatible grafting layer. This ensures that the modified UV-resistant composite remains dispersed and stable in the silicone rubber raw material and does not cause catalyst deactivation, crosslinking delay, or precipitation migration in the vulcanization system, thereby endowing the silicone rubber material with continuous UV aging resistance.

[0015] Furthermore, in step S3, the pH is adjusted to 9.0-10.0 using ammonia water with a mass fraction of 25%, and in step S5, the pH is adjusted to 4.5-5.5 using glacial acetic acid with a mass fraction of 10%.

[0016] Furthermore, the average particle size of the sericite powder is 10-15 μm.

[0017] Furthermore, the raw silicone rubber is methyl vinyl silicone rubber with a vinyl molar content of 0.05-0.30% and a number average molecular weight of 450,000-750,000.

[0018] Furthermore, the reinforcing filler is one or more of fumed silica and precipitated silica, with a specific surface area of ​​150-300 m². 2 / g.

[0019] Furthermore, the structuring control agent is one or a combination of two or more of hydroxyl silicone oil, diphenylsilanediol, or hexamethyldisilazane.

[0020] Furthermore, the crosslinking agent is a hydrogen-containing silicone oil, and the hydrogen content of the hydrogen-containing silicone oil is 0.20-0.80 wt%.

[0021] Furthermore, the catalyst is one of chloroplatinic acid, Karstedt catalyst, and Speier catalyst.

[0022] Furthermore, the inhibitor is one or a combination of two or more of 1-ethynylcyclohexanol, 3-methyl-1-butyn-3-ol, or tetramethyltetravinylcyclotetrasiloxane.

[0023] Furthermore, silicone oil, liquid silicone rubber, MQ silicone resin, etc., may also be added to the aforementioned advanced manufacturing UV-resistant silicone rubber material.

[0024] A method for preparing an advanced manufacturing UV-resistant silicone rubber material includes the following steps: A1. Add the raw silicone rubber, reinforcing filler and structuring control agent to a kneader, knead at 40-70℃ for 30-60 min, raise the temperature to 120-160℃, and heat treat under vacuum conditions of -0.08MPa~-0.095MPa for 1-2 h to obtain the basic compound. A2. Cool the base compound to 40-60°C, add the modified UV-resistant compound, and mix in a two-roll mill or internal mixer for 10-25 minutes to disperse the modified UV-resistant compound in the base compound, thereby obtaining a UV-resistant masterbatch. A3. Cool the UV-resistant masterbatch to 25-35℃, add the crosslinking agent, inhibitor and catalyst in sequence, turn and roll and pass through thinly 5-10 times to mix it evenly, and then cut it into sheets to obtain the rubber material to be vulcanized. A4. After the rubber material to be vulcanized is left to stand, it is placed in a mold at a set temperature and subjected to pressure by a flat vulcanizing machine for a first-stage vulcanization. After demolding, it is placed in a forced-air drying oven for a second-stage vulcanization, thus obtaining an advanced manufacturing UV-resistant silicone rubber material.

[0025] Furthermore, in step A4, the conditions for the first-stage vulcanization molding are: vulcanization temperature of 140-160℃, vulcanization pressure of 10-20MPa, and vulcanization time of 5-15min; the conditions for the second-stage vulcanization are: vulcanization temperature of 180-200℃ and vulcanization time of 2-4h.

[0026] This invention significantly improves the UV aging resistance of silicone rubber during long-term outdoor service by constructing a multi-layered core-shell structure modified UV-resistant composite. Methyl vinyl silicone rubber is used as a continuous elastic matrix, combined with silica and a structure control agent to ensure mechanical strength, processing stability, and resistance to filler structure formation. The modified composite uses sericite as a core, utilizing its sheet-like structure to form a UV-reflective layer and a tortuous blocking path, reducing UV penetration. A ZnO-CeO2 composite nanolayer is in-situ loaded on the surface to achieve broad-spectrum absorption and shielding of UVA and UVB bands. An outer SiO2 passivation layer isolates the semiconductor oxide from the silicone rubber molecular chains, inhibiting photocatalytic degradation under UV excitation. Benzotriazole and benzophenone UV-absorbing groups are grafted onto the SiO2 surface to further absorb residual UV energy and avoid the migration, precipitation, and poor durability problems of traditional organic absorbers. Meanwhile, the compatibility of vinylsilane and polydimethylsiloxane segments enhances the interfacial affinity between the composite and the silicone rubber matrix, stabilizing its dispersion and making it suitable for hydrogen-containing silicone oil / platinum catalytic addition crosslinking systems. By using crosslinking agents, catalysts, and inhibitors to regulate the vulcanization rate and crosslinking density, the material exhibits excellent processability, mechanical properties, and long-lasting UV aging resistance, making it suitable for long-term exposure applications such as photovoltaic encapsulation, aerospace protection, and outdoor sealing.

[0027] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention utilizes the physical reflection and tortuous blocking of the sericite sheet-like core, the broad-spectrum chemical absorption of the ZnO-CeO2 composite nanolayer, and the synergistic effect of the outer organic ultraviolet absorbing groups to achieve a more complete shielding coverage of the UVA and UVB bands. At the same time, the organic ultraviolet absorbing groups are chemically grafted and fixed on the surface of the composite, significantly reducing the tendency for migration and precipitation, and improving the durability of ultraviolet protection.

[0028] 2. The SiO2 passivation layer effectively isolates the semiconductor oxide ultraviolet absorption layer from the silicone rubber molecular chain, thereby reducing the catalytic activity of photogenerated electron-hole pairs in inducing the breakage of the silicone rubber main chain and the oxidation of side groups. This solves the technical contradiction that traditional inorganic nano-shielding agents accelerate the aging of the matrix under ultraviolet excitation.

[0029] 3. The vinylsilane and polydimethylsiloxane compatible segments introduced into the outer layer of the core-shell structure enhance the interfacial affinity between the modified UV-resistant composite and the silicone rubber matrix, thereby improving the mixing and dispersion stability. At the same time, the core-shell structure avoids deactivation or delayed crosslinking caused by direct contact between the filler and the platinum-based catalyst, and the integrity of the vulcanization network tends to be maintained, thus slowing down the decline in mechanical properties while the material is functionalized. Attached Figure Description

[0030] Figure 1 SEM image of the modified UV-resistant composite prepared in Example 1 of this invention. Detailed Implementation

[0031] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are merely some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0032] Preparation Example 1: Preparation of modified UV-resistant composite: 1. Raw material weight parts: 40 parts sericite powder, 23 parts zinc acetate dihydrate, 5 parts cerium nitrate hexahydrate, 14 parts urea, 28 parts tetraethyl orthosilicate, 4.5 parts γ-glycidyl etheroxypropyltrimethoxysilane, 6 parts 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 3.5 parts 2,4-dihydroxybenzophenone, 3 parts vinyltriethoxysilane, 9 parts hydroxyl-terminated polydimethylsiloxane, and 0.5 parts potassium carbonate.

[0033] The 3wt% sodium hydroxide aqueous dispersion is used as a process solution for sericite surface treatment and is not limited to the dry basis component content of the modified UV-resistant composite.

[0034] The deionized water and anhydrous ethanol used in the steps are process solvents for dispersion, washing and crosslinking. They are basically removed after drying and are not used as a limit for the dry basis component content of the modified UV-resistant composite.

[0035] The sericite powder has an average particle size of 12μm and was purchased from Anhui Gree New Material Technology Co., Ltd., model GA-5.

[0036] The hydroxyl-terminated polydimethylsiloxane has a viscosity of 70 mPa·s and was purchased from Jiangsu Kexing New Materials Co., Ltd., model F-007.

[0037] 2. Preparation method: S1. Add 40 parts of sericite powder to 400 parts of 3wt% sodium hydroxide aqueous dispersion, control the solid-liquid mass ratio to 1:10, heat to 60℃ in air atmosphere, stir at 500r / min for 2h, after the reaction is completed, filter, wash the filter cake with deionized water 5 times, the pH of the last filtrate is 7.4, place the washed filter cake in a 90℃ forced air drying oven and dry for 5h, after drying, pulverize and pass through a 1000-mesh sieve to obtain 38.4 parts of surface hydroxylated flake sericite.

[0038] S2. Add 38.4 parts of the surface-hydroxylated flake sericite obtained in S1 to a water-alcohol mixture consisting of 179.2 parts of deionized water and 358.4 parts of anhydrous ethanol, controlling the solid-liquid mass ratio of the surface-hydroxylated flake sericite to the water-alcohol mixture to be 1:14. Stir for 10 min at 25℃ and 800 r / min under air atmosphere, then ultrasonically disperse for 30 min. Subsequently, add 23 parts of zinc acetate dihydrate, 5 parts of cerium nitrate hexahydrate, and 14 parts of urea in sequence. The system was heated to 84℃ and stirred at 800 r / min for 4 h. After the reaction was completed, the mixture was filtered. The filter cake was washed three times with deionized water and then twice with anhydrous ethanol. The washed filter cake was placed in a 110℃ forced-air drying oven and dried for 4 h. Then it was transferred to a muffle furnace and calcined at 330℃ at 5℃ / min for 2 h. After naturally cooling to room temperature, it was taken out to obtain 48.6 parts of sheet-like composite cores with ZnO-CeO2 synergistic ultraviolet absorption layer on the surface.

[0039] S3. Add 48.6 parts of the sheet-like composite core obtained in S2 to a system composed of 81 parts of deionized water and 405 parts of anhydrous ethanol. The solid-liquid mass ratio of the sheet-like composite core to the alkaline aqueous alcohol system is 1:10. Adjust the pH of the system to 9.5 with 25% ammonia water. Adjust the temperature of the system to 40℃ and stir at 650 r / min for 10 min in an air atmosphere. Then, place 28 parts of tetraethyl orthosilicate in a dropping funnel and add it dropwise to the above dispersion at a dropping rate of 0.8 mL / min. Maintain the temperature at 40℃ during the dropping process. After the dropping is completed, continue the reaction for 4 h, then stop stirring and age at 40℃ for 3 h. After aging, filter, wash the filter cake three times with anhydrous ethanol, and dry it in a 100℃ forced-air drying oven for 5 h to obtain 55.8 parts of the sheet-like core-shell intermediate with a silica passivation layer.

[0040] S4. Under nitrogen protection, 6 parts of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 3.5 parts of 2,4-dihydroxybenzophenone, 4.5 parts of γ-glycidyl etheroxypropyltrimethoxysilane, and 0.5 parts of potassium carbonate were added to anhydrous ethanol. The total mass ratio of the above reactants to anhydrous ethanol was controlled at 1:9. The temperature was raised to 78°C, and the mixture was stirred at 400 r / min for 3 h. After the reaction was completed, the mixture was cooled to 30°C. The insoluble potassium carbonate and trace solid impurities were removed by filtration through a 0.45 μm polytetrafluoroethylene filter membrane to obtain 143 parts of a composite organic UV absorption modified liquid containing silane end groups.

[0041] S5. The plate-like core-shell intermediate obtained in S3 was added to the composite organic UV absorption modification solution with silane end groups obtained in S4, and then 160 parts of anhydrous ethanol were added. The mixture was stirred and dispersed at 25℃ and 600 r / min for 20 min. The pH of the system was adjusted to 5.0 with 10% glacial acetic acid. Then, 3 parts of vinyltriethoxysilane were added at a dropping rate of 0.3 mL / min, and 9 parts of hydroxyl-terminated polydimethylsiloxane were added at a dropping rate of 0.6 mL / min. After the addition was completed, the system was heated to 72℃ and grafted at 600 r / min in air for 5.5 h. After the reaction was completed, the slurry was cooled to 35℃ and filtered. The resulting filter cake was washed 4 times with anhydrous ethanol until the filtrate was colorless. The washed filter cake was placed in a vacuum drying oven at 95℃ and dried at a vacuum of -0.090 MPa for 8 h. The dried product was pulverized by air jet and passed through a 1000-mesh sieve to obtain 67 parts of modified UV-resistant composite.

[0042] Depend on Figure 1 As can be seen, the particles in the figure have obvious flaky and layered block morphology, and the particle size scale matches the average particle size of sericite powder in Preparation Example 1, which is about 12 μm, and the 5 μm scale in the figure. The surface of the flaky matrix is ​​relatively rough and has small particles / protrusions distributed on it, which is consistent with the morphological characteristics of the composite filler after in-situ loading of ZnO-CeO2 composite nanolayer, followed by SiO2 passivation layer and organic modification coating.

[0043] Comparative preparation example 1: The modified UV-resistant composite was prepared by referring to the preparation method in Preparation Example 1, except that the sericite powder was replaced with an equal mass of kaolin powder, and everything else remained the same as in Preparation Example 1.

[0044] Comparative preparation example 2: The modified UV-resistant composite was prepared by referring to the preparation method in Preparation Example 1, except that cerium nitrate hexahydrate was replaced with an equal mass of zinc acetate dihydrate, and everything else remained the same as in Preparation Example 1.

[0045] Comparative preparation example 3: The modified UV-resistant complex was prepared by referring to the preparation method in Preparation Example 1, except that zinc acetate dihydrate was replaced with an equal mass of cerium nitrate hexahydrate, and everything else remained the same as in Preparation Example 1.

[0046] Comparative preparation example 4: The modified UV-resistant composite was prepared by referring to the preparation method in Preparation Example 1, except that the hydroxyl-terminated polydimethylsiloxane was replaced with an equal amount of methyl silicone oil, and everything else remained the same as in Preparation Example 1.

[0047] Comparative preparation example 5: The modified UV-resistant composite was prepared by referring to the preparation method in Preparation Example 1, except that the calcination temperature in step S2 was adjusted from 330°C to 200°C, and the rest remained the same as in Preparation Example 1.

[0048] Comparative preparation example 6: The modified UV-resistant composite was prepared by referring to the preparation method in Preparation Example 1, except that tetraethyl orthosilicate was replaced with an equal mass of methyltriethoxysilane, and everything else remained the same as in Preparation Example 1.

[0049] Comparative preparation example 7: The modified UV-resistant complex was prepared by referring to the preparation method in Preparation Example 1, except that γ-glycidoxypropyltrimethoxysilane was replaced with an equal mass of 3-aminopropyltrimethoxysilane, and the rest remained the same as in Preparation Example 1.

[0050] Example 1: Preparation of an advanced manufacturing UV-resistant silicone rubber material: 1. Raw material weight parts: 100 parts of raw silicone rubber, 32 parts of reinforcing filler, 4.5 parts of structure control agent, 2.5 parts of crosslinking agent, 0.2 parts of catalyst, 0.08 parts of inhibitor, and 6 parts of modified UV-resistant compound.

[0051] The raw silicone rubber is methyl vinyl silicone rubber with a vinyl molar content of 0.15% and a number-average molecular weight of 650,000. It was purchased from Dongjue Organosilicon (Nanjing) Co., Ltd., model 110-2.

[0052] The reinforcing filler is fumed silica with a specific surface area of ​​200±20 m². 2 / g, purchased from Zhejiang Fujit Group Co., Ltd., model FST200.

[0053] The structuring control agent is hydroxyl silicone oil.

[0054] The crosslinking agent is a hydrogen-containing silicone oil with a hydrogen content of 0.36 wt%, purchased from Jiangsu Kexing New Materials Co., Ltd., model SH-36.

[0055] The catalyst is a Karstedt catalyst with a platinum content of 3000 ppm, purchased from Beijing Huawi Ruike Chemical Technology Co., Ltd., model HWG53972.

[0056] The inhibitor is 1-ethynylcyclohexanol.

[0057] The modified UV-resistant compound is the modified UV-resistant compound prepared in Preparation Example 1.

[0058] 2. Preparation method: A1. Add 100 parts of methyl vinyl silicone rubber to a kneading device, control the material temperature at 55℃ in an air atmosphere, and knead at 25r / min for 10min. Then, add 32 parts of fumed silica and 4.5 parts of hydroxyl silicone oil in equal parts to the device. After each addition, continue kneading at 55℃ and 25r / min for 5min. After all raw materials are added, continue kneading at 55℃ and 30r / min for 10min. Then, raise the material temperature to 145℃, control the system vacuum degree to -0.090MPa, and heat treat at 145℃ and 30r / min for 1.5h to obtain the basic compound.

[0059] A2. Cool the base compound to 50°C and mix it in air at 25 r / min. Divide the 6 parts of the modified UV-resistant compound into 2 equal parts and add them to the base compound. After each part is added, continue mixing for 4 min. After all the parts are added, continue mixing at 50°C and 25 r / min for 6 min to obtain the UV-resistant masterbatch.

[0060] A3. Cool the UV-resistant masterbatch to 30°C and mix it on an open mill. Control the front roller speed at 18 r / min and the rear roller speed at 22 r / min. Control the initial roller gap at 1.5 mm. First, add 2.5 parts of hydrogen-containing silicone oil to the UV-resistant masterbatch. Then, melt 0.08 parts of 1-ethynylcyclohexanol at 35°C beforehand and add it within 1 minute. Then add 0.2 parts of Karstedt catalyst. After all the catalyst is added, continue mixing for 10 minutes. Adjust the roller gap to 1.0 mm, tumble and roll, and pass through 8 times. During the mixing process, control the temperature of the rubber compound below 35°C. Sheet the rubber compound to be vulcanized.

[0061] A4. The rubber compound to be vulcanized is left to stand for 12 hours at 25°C and 50% relative humidity. The vulcanized rubber compound is then placed in a mold and vulcanized for 10 minutes at 150°C and 15MPa. After vulcanization, the product is demolded and placed in a forced-air drying environment for a second vulcanization at 190°C for 3 hours. After the second vulcanization, the product is cooled to room temperature to obtain an advanced manufacturing UV-resistant silicone rubber material.

[0062] Example 2: The preparation of an advanced manufacturing UV-resistant silicone rubber material is carried out by referring to the preparation method in Example 1, except that the fumed silica is replaced with an equal mass of precipitated silica, and the rest is the same as in Example 1.

[0063] Example 3: The preparation of an advanced manufacturing UV-resistant silicone rubber material is carried out by referring to the preparation method in Example 1, except that the hydroxyl silicone oil is replaced with an equal mass of diphenylsilanediol, and the rest is the same as in Example 1.

[0064] Example 4: The preparation of an advanced manufacturing UV-resistant silicone rubber material is carried out by referring to the preparation method in Example 1, except that 1-ethynylcyclohexanol is replaced with an equal mass of 3-methyl-1-butyn-3-ol, and the rest is the same as in Example 1.

[0065] Comparative Examples 1-7: The preparation of an advanced manufacturing UV-resistant silicone rubber material is carried out by referring to the preparation method in Example 1, except that the modified UV-resistant compound is replaced with the modified UV-resistant compound prepared in Comparative Preparation Examples 1-7, and the rest is the same as in Example 1.

[0066] Comparative Example 8: The preparation of an advanced manufacturing UV-resistant silicone rubber material is carried out by referring to the preparation method in Example 1, except that the modified UV-resistant compound is replaced with an equal mass of nano zinc oxide, and the rest remains the same as in Example 1.

[0067] Comparative Example 9: The preparation of an advanced manufacturing UV-resistant silicone rubber material is carried out by referring to the preparation method in Example 1, except that "the UV-resistant masterbatch is cooled to 30°C" and "the temperature of the rubber compound is controlled below 35°C during the mixing process" are adjusted to "the UV-resistant masterbatch is cooled to 60°C and mixed on an open mill, and the temperature of the rubber compound is controlled at 65-75°C during the mixing process", and the rest remains the same as in Example 1.

[0068] Comparative Example 10: The preparation of an advanced manufacturing UV-resistant silicone rubber material is carried out by referring to the preparation method in Example 1, except that the vulcanization conditions of the first stage of A4 are adjusted to vulcanization temperature of 100°C, vulcanization pressure of 5MPa, and vulcanization time of 5min, while other conditions remain the same as in Example 1.

[0069] Performance testing: 1. Mechanical property testing: The silicone rubber materials obtained in Examples 1-4 and Comparative Examples 1-10 were respectively made into vulcanized sheets with a thickness of 2.0 mm and cut into corresponding test specimens.

[0070] Tensile strength and elongation at break were tested in accordance with GB / T528-2009, using dumbbell-shaped specimens, and the tensile strength and elongation at break of each specimen were recorded.

[0071] Tear strength was tested in accordance with GB / T529-2008, using right-angled specimens, and the tear strength of each specimen was recorded.

[0072] The Shore A hardness was tested according to GB / T39693.4-2025, and the effective thickness of the hardness test sample was 10 mm.

[0073] 2. UV aging resistance test: The silicone rubber materials obtained in Examples 1-4 and Comparative Examples 1-10 were made into samples for mechanical property testing, and each group of samples was randomly divided into an unaged group and a UV-aged group.

[0074] The ultraviolet aging test was conducted in accordance with GB / T16585-1996. The ultraviolet aging group samples were subjected to cyclic irradiation and condensation treatment using a fluorescent ultraviolet lamp artificial climate aging chamber, with a cumulative aging time of 1500 hours.

[0075] After UV aging, the samples were removed and conditioned according to GB / T2941-2025. Subsequently, the tensile strength of the UV-aged samples was determined according to the aforementioned basic mechanical property test methods, and the tensile strength retention rate was calculated as P. t / P0×100%, where P0 is the tensile strength test value of the sample before UV aging, P t The tensile strength test value is the value of the sample after UV aging for a specified time.

[0076] The test results are shown in Table 1.

[0077] Table 1. Performance Test Results Table 1 shows that the silicone rubber materials in Examples 1-4 exhibited superior overall performance in terms of initial mechanical properties and tensile strength retention after UV aging. This is attributed to the multilayer core-shell structure, which uses sericite as a sheet-like core, ZnO-CeO2 as a composite UV absorption layer, SiO2 as a passivation and isolation layer, and is grafted with organic UV absorption groups and polydimethylsiloxane compatible segments. The comparative examples, due to changes in core type, disruption of absorption layer synergy, lack of compatible segments, improper calcination or vulcanization processes, unstable dispersion caused by direct addition of nanoparticles, or the introduction of aminosilanes interfering with platinum catalysis, exhibited defects in UV shielding, interfacial bonding, crosslinking network integrity, or photocatalytic inhibition, leading to performance degradation. These results indicate that the synergistic shielding, interfacial compatibility, passivation and isolation, and dispersion stabilization effects among the functional layers of the core-shell structure are crucial in determining the mechanical properties and UV aging resistance of silicone rubber.

[0078] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. An advanced manufacturing UV-resistant silicone rubber material, characterized in that, By weight, it includes the following components: 100 parts of silicone rubber raw rubber, 25-40 parts of reinforcing filler, 3-6 parts of structure control agent, 2-4 parts of crosslinking agent, 0.1-0.3 parts of catalyst, 0.06-0.12 parts of inhibitor, and 4-8 parts of modified UV-resistant compound; The modified UV-resistant composite has a core-shell composite structure with sericite as the core. The surface of the core is loaded with a ZnO-CeO2 composite nanolayer. The ZnO-CeO2 composite nanolayer is coated with a SiO2 passivation layer. The surface of the SiO2 passivation layer is grafted with benzotriazole and benzophenone organic UV-absorbing groups and contains vinylsilane and polydimethylsiloxane compatible segments.

2. The UV-resistant silicone rubber material for advanced manufacturing according to claim 1, characterized in that, The modified UV-resistant composite comprises, by weight, the following components: 35-45 parts sericite powder, 18-28 parts zinc acetate dihydrate, 3-8 parts cerium nitrate hexahydrate, 10-18 parts urea, 20-35 parts tetraethyl orthosilicate, 3-6 parts γ-glycidyl etheroxypropyltrimethoxysilane, 4-8 parts 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-5 parts 2,4-dihydroxybenzophenone, 2-4 parts vinyltriethoxysilane, 6-12 parts hydroxyl-terminated polydimethylsiloxane, and 0.3-0.8 parts potassium carbonate.

3. The UV-resistant silicone rubber material for advanced manufacturing according to claim 2, characterized in that, The preparation method of the modified UV-resistant composite includes the following steps: S1. The sericite powder is added to the sodium hydroxide aqueous dispersion with a mass concentration of 3wt%, and the solid-liquid ratio is controlled at 1:

10. The mixture is stirred for 1.5-3 hours at 50-65℃ and 400-600 r / min. After filtration, the mixture is washed with deionized water until the pH of the filtrate is 7.0-8.

0. Then, it is dried at 80-100℃ for 4-6 hours and passed through an 800-1250 mesh sieve to obtain surface-hydroxylated flake sericite. S2. The surface-hydroxylated flaky sericite is dispersed in a mixture of deionized water and anhydrous ethanol in a mass ratio of 1:2, with the solid-liquid ratio controlled at 1:

14. The mixture is stirred and ultrasonically dispersed at 600-900 r / min for 20-40 min. The zinc acetate dihydrate, cerium nitrate hexahydrate, and urea are added, and the temperature is raised to 78-88℃. The reaction is carried out for 3-5 h. After the reaction is completed, the mixture is filtered, washed, and dried at 100-120℃ for 3-5 h. Then, it is calcined at 300-360℃ for 1.5-2.5 h to obtain a flaky composite core with an in-situ ZnO-CeO2 synergistic ultraviolet absorption layer on the surface. S3. The sheet-like composite core is added to a system composed of deionized water and anhydrous ethanol in a mass ratio of 1:5, the solid-liquid ratio is controlled at 1:10, the pH of the system is adjusted to 9.0-10.0, the temperature is 35-45℃, the stirring speed is 500-800 r / min, and the tetraethyl orthosilicate is added dropwise at a rate of 0.5-1.0 mL / min. After the addition is completed, the reaction continues for 3-5 h, and then it is allowed to stand for aging for 2-4 h. After filtration, washing with ethanol and drying at 90-110℃ for 4-6 h, a sheet-like core-shell intermediate with a silica passivation layer is obtained. S4. Under nitrogen protection, the 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2,4-dihydroxybenzophenone, γ-glycidoxypropyltrimethoxysilane and potassium carbonate are added to anhydrous ethanol, the solid-liquid ratio is controlled at 1:9, and the reaction is carried out at 70-82℃ and 300-500r / min for 2-4h. After cooling, the insoluble matter is removed by filtration to obtain a composite organic UV absorption modified liquid containing silane end groups. S5. Disperse the plate-like core-shell intermediate in the composite organic UV absorption modification solution, adjust the pH of the system to 4.5-5.5, add the vinyltriethoxysilane and hydroxyl-terminated polydimethylsiloxane dropwise, and graft and coat the mixture at 65-78℃ and 500-700r / min for 4-7h. Then filter, wash with anhydrous ethanol until the filtrate is colorless, vacuum dry at 85-105℃ for 6-10h, pulverize and pass through an 800-1250 mesh sieve to obtain the modified UV-resistant composite.

4. The UV-resistant silicone rubber material for advanced manufacturing according to claim 2, characterized in that, The average particle size of the sericite powder is 10-15 μm.

5. The UV-resistant silicone rubber material for advanced manufacturing according to claim 1, characterized in that, The raw silicone rubber is methyl vinyl silicone rubber with a vinyl molar content of 0.05-0.30%.

6. The UV-resistant silicone rubber material for advanced manufacturing according to claim 1, characterized in that, The reinforcing filler is one or more of fumed silica and precipitated silica, with a specific surface area of ​​150-300 m². 2 / g.

7. The UV-resistant silicone rubber material for advanced manufacturing according to claim 1, characterized in that, The structuring control agent is one or a combination of two or more of hydroxyl silicone oil, diphenylsilanediol, or hexamethyldisilazane.

8. The UV-resistant silicone rubber material for advanced manufacturing according to claim 1, characterized in that, The crosslinking agent is a hydrogen-containing silicone oil, and the hydrogen content of the hydrogen-containing silicone oil is 0.20-0.80 wt%. The catalyst is one of chloroplatinic acid, Karstedt catalyst, and Speier catalyst; The inhibitor is one or a combination of two or more of 1-ethynylcyclohexanol, 3-methyl-1-butyn-3-ol, or tetramethyltetravinylcyclotetrasiloxane.

9. A method for preparing an advanced manufacturing UV-resistant silicone rubber material according to any one of claims 1-8, characterized in that, Includes the following steps: A1. Add the raw silicone rubber, reinforcing filler and structuring control agent to a kneader, knead at 40-70℃ for 30-60 min, raise the temperature to 120-160℃, and heat treat under vacuum conditions of -0.08MPa~-0.095MPa for 1-2 h to obtain the basic compound. A2. Cool the base compound to 40-60°C, add the modified UV-resistant compound, and mix in a two-roll mill or internal mixer for 10-25 minutes to disperse the modified UV-resistant compound in the base compound, thereby obtaining a UV-resistant masterbatch. A3. Cool the UV-resistant masterbatch to 25-35℃, add the crosslinking agent, inhibitor and catalyst in sequence, turn and roll and pass through thinly 5-10 times to mix it evenly, and then cut it into sheets to obtain the rubber material to be vulcanized. A4. After the rubber material to be vulcanized is left to stand, it is placed in a mold at a set temperature and subjected to pressure by a flat vulcanizing machine for a first-stage vulcanization. After demolding, it is placed in a forced-air drying oven for a second-stage vulcanization, thus obtaining an advanced manufacturing UV-resistant silicone rubber material.

10. The method for preparing an advanced manufacturing UV-resistant silicone rubber material according to claim 9, characterized in that, In step A4, the conditions for the first-stage vulcanization are: vulcanization temperature of 140-160℃, vulcanization pressure of 10-20MPa, and vulcanization time of 5-15min; the conditions for the second-stage vulcanization are: vulcanization temperature of 180-200℃ and vulcanization time of 2-4h.